Utility and usability evaluation of an information diary tool to measure health information access and exposure among patients with high cardiovascular risk - Lim, Hooi Min; Ng, Chirk Jenn; Abdullah, Adina; Dalmazzo, Jason; Lim, Woei Xian; Lee, Kah Hang; Dunn, Adam G. (Frontiers in Public Health, 2023)
Background: Online health misinformation about statins potentially affects health decision-making on statin use and adherence. We developed an information diary platform (IDP) to measure topic-specific health information exposure where participants record what information they encounter. We evaluated the utility and usability of the smartphone diary from the participants’ perspective. Methods: We used a mixed-method design to evaluate how participants used the smartphone diary tool and their perspectives on usability. Participants were high cardiovascular-risk patients recruited from a primary care clinic and used the tool for a week. We measured usability with the System Usability Scale (SUS) questionnaire and interviewed participants to explore utility and usability issues. Results: The information diary was available in three languages and tested with 24 participants. The mean SUS score was 69.8±12.9. Five themes related to utility were: IDP functions as a health information diary; supporting discussion of health information with doctors; wanting a feedback function about credible information; increasing awareness of the need to appraise information; and wanting to compare levels of trust with other participants or experts. Four themes related to usability were: ease of learning and use; confusion about selecting the category of information source; capturing offline information by uploading photos; and recording their level of trust. Conclusion: We found that the smartphone diary can be used as a research instrument to record relevant examples of information exposure. It potentially modifies how people seek and appraise topic-specific health information.